William Morris and his work - Kimball, Ned (My University, 1902)
Introduction: Writer, inventor, artist, sculptor, translator and politician, a man well schooled in many things, though absolutely perfect in none, a man of high character, of an even temper and of kind disposition; a man with many warm friends and bitter enemies, such was William Morris. Morris, one of the most important characters of the nineteenth century, is not widely studied although there is no obvious reason for this. It is the purpose of this treatise to take up the most important points in Mr. Morris’s life and to show forth his genius in its true light.
Citation: Kimball, Ned. William Morris and his work. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: William Morris; Writer; Artist; Humanitarian; Theses; Manuscripts (documents)